Monk Fruit is a Safe, Natural, Non-Caloric Sweetener in Individuals with Type 2 Diabetes - Lavalle-Gonzalez Fernando Javier; Rios-Ortega Adriana Gabriela; Mancillas-Adame Leonardo G.; Contreras-Arce Alan; Díaz-Hernández Adan F.; Santos Morales Karla A.; Partida Adriana Patricia (International Journal of Nutrition, 2023)
Non-nutritive sweeteners are used as adjuncts in treating patients with diabetes to reduce carbohydrate intake. Monk fruit is an FDA-approved1 natural NNS2-. There is no information regarding the use of monk fruit in individuals with T2DM3. The primary objective was to compare the glycemic response to sucrose and monk fruit in individuals with and without T2DM. Twenty-six individuals with T2DM and 29 without DM4 underwent two oral glucose tolerance tests5 after a 250-ml sucrose- or monk fruit-sweetened beverage. Glucose levels were measured at 0, 30, 60, 90, and 120 minutes. An appetite scale was used before and after the procedure. Insulin levels were measured in ten randomly selected individuals from the control group. The glucose levels at 30 and 120 min were significantly lower in both groups in the monk fruit-OGTT. There was a peak response in the T2DM group at 90 min (median, IQR, 247 mg/dL, 203-293) with the sucrose OGTT, while no peak response was seen in the monk fruit OGTT. There were no differences between sweeteners in terms of appetite evaluation. The postprandial effect on insulin levels was flat with the monk fruit-sweetened beverage. In contrast, there was a significantly higher spike with the sucrose-sweetened beverage. In conclusion, monk fruit does not increase glucose levels in individuals with T2DM; thus, it could be a safe alternative as a substitute food sweetener.
Keywords: non-caloric sweeteners